Emotional stability as a component in future professionals' psychological well-being - Курова, Анастасія Володимирівна; Курова, А. В.; Курова, Анастасия Владимировна; Kurova, Anastasiia V.; Галян, Ігор Михайлович; Галян, І. М.; Галян, Игорь Михайлович; Halian, Ihor M.; Склярук, Анастасія Володимирівна; Склярук, А. В.; Склярук, Анастасия Владимировна; Skliaruk, Anastasiia V.; et al. (Editorial Primmate S. A. S., 2022)
The study was carried out to theoretically and empirically support the factors of emotional stability as a systemic quality of the individual, which helps future professionals in professional self-determination to effectively adapt to the educational space and contributes to the development of a sense of psychological well-being. Students (n = 277) of different years of studies (nI=112; nIII=97; nV=68), who received higher education in socionomic specialties, participated in the study. Psychodiagnostic techniques were used, which are valid and reliable. The connection between emotional stability and self-actualization was studied during the following years of studies: 1 year (rs=.216; p<.05); III (rs=.346; p<.001); V (rs=.411; p<.001). The growth of emotional stability (C) was recorded (t = -3.301; p <. 0021), anxiety (O) (t = -2.682; p <.0015) and expressiveness (F) (t = -2.916; p <.0034). The correlation between the socio-psychological adaptation and the emotional stability of the respondents was established: I (rs = .432; p <.001); III (rs = .331; p < .001); V (rs = .422; p < .001). It is empirically substantiated and approved that psychological well-being is based on the idea of constant need and man's capacity for self-development and self-realization.

Дослідження проводилося з метою теоретичного та емпіричного підтвердження чинників емоційної стійкості як системної якості особистості, що допомагає майбутнім фахівцям у професійному самовизначенні ефективно адаптуватися в освітньому просторі та сприяє розвитку почуття психологічного благополуччя. У дослідженні брали участь студенти (n = 277) різних років навчання (nI=112; nIII=97; nV=68), які здобули вищу освіту за соціономічними спеціальностями. Були використані психодіагностичні методики, які є дійсними та надійними. Зв'язок емоційної стійкості та самоактуалізації вивчався протягом наступних років навчання: 1 рік (rs=.216; p<.05); III (rs=.346; p<.001); V (rs=.411; p<.001). Зафіксовано зростання емоційної стійкості (C) (t = -3,301; p <. 0021), тривожності (O) (t = -2,682; p <,0015) та експресивності (F) (t = -2,916; p < .0034). Встановлено кореляцію між соціально-психологічною адаптацією та емоційною стійкістю респондентів: I (rs = ,432; p <,001); III (rs = .331; p < .001); V (rs = .422; p < .001). Емпірично обґрунтовано та підтверджено, що психологічне благополуччя ґрунтується на ідеї постійної потреби та здатності людини до саморозвитку та самореалізації.
Halian I. Emotional stability as a component in future professionals' psychological well-being / I. Halian, A. Kurova, A. Skliaruk, O. Halian, A. Khokhlov // Amazonia Investiga. – Vol. 11. – Iss. 51. – Editorial Primmate S. A. S., 2022. – P. 183-196.
Keywords: professional congruence; emotional stability; adaption; self-actualization; psychological well-being; професійна конгруентність; емоційна стійкість; адаптація; самореалізація; психологічне самопочуття; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology